GROUPING FORMATION OF THE NATIONAL GUARD TO PERFORM THE TASKS OF STATE DEFENSE - Shmakov, О. М.; Poliakov, V. Yu. (Honor and Law, 2019)
The role of operational tasks in defining operational alignment elements forming NG Ukraine and their battle staff. An option grouping of operational and territorial associations NG Ukraine to perform tasks of defense.